2010
DOI: 10.3389/fnins.2010.00055
|View full text |Cite
|
Sign up to set email alerts
|

The influence of psychological state and motivation on brain-computer interface performance in patients with amyotrophic lateral sclerosis - a longitudinal study

Abstract: The current study investigated the effects of psychological well-being measured as quality of life (QoL), depression, current mood and motivation on brain–computer interface (BCI) performance in amyotrophic lateral sclerosis (ALS). Six participants with most advanced ALS were trained either for a block of 20 sessions with a BCI based on sensorimotor rhythms (SMR) or a block of 10 sessions with a BCI based on event-related potentials, or both. Questionnaires assessed QoL and severity of depressive symptoms befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
173
2
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(182 citation statements)
references
References 80 publications
5
173
2
2
Order By: Relevance
“…In a longitudinal study, motivational factors were shown to be correlated with BCI performance on participants with amyotrophic lateral sclerosis (ALS) [14]. Other studies have focused on neurophysiological markers.…”
Section: Introductionmentioning
confidence: 99%
“…In a longitudinal study, motivational factors were shown to be correlated with BCI performance on participants with amyotrophic lateral sclerosis (ALS) [14]. Other studies have focused on neurophysiological markers.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the intra-subject performance variation is less often investigated. Studies on this issue are dedicated to psychological aspects [27] or neurophysiological markers [21]- [23], [28]- [30]. In the latter case, efforts have been made for identifying neural correlates for performance variation extracted from EEG oscillations in different frequency bands and brain regions.…”
Section: Introductionmentioning
confidence: 99%
“…The P300 has been exploited in many ways to produce a number of functional applications [6,7]. Although the specific technology used for recording the brain activity is closely tied to the final performance of the classifier used, [8,9] demonstrated that training and motivation have a positive and visible impact on the shape and appearance of the P300. Experimental setups using EEG and the P300 have been widely used in the development of BCI [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%